CHARACTERISTICS OF LIMESTONES FROM THE CIBODAS FORMATION AND CIKARANG MEMBER OF JAMPANG FORMATION IN CIKANGKUNG AREA, SUKABUMI REGENCY, WEST JAVA - Maulana, Muhammad Hafidz; Pratiwi, Santi Dwi (Bulletin of Scientific Contribution, 2024)
This research aims to identify the lithological characteristics as well as the occurrence of larger benthic foraminifera in limestone from the Cikangkung and surrounding area, Sukabumi Regency with coordinates between 106°25'40.707" E to 106°28'23.581" E and 7°19'00.738" S to 7°21'12.833" S. The area is predominantly by rock units belonging to the Cikarang Member of the Jampang Formation and the Cibodas Formation. With focuses on classifying limestone and distinguishing the limestone from those two formations through petrographic characteristics, and microfossil analysis, four types of limestone were identified as tuffaceous limestone, grainstone, packstone, and boundstone. Petrographic analysis shows compositional differences in the tuffaceous limestone, which contains pyroclastic materials such as glass, silica minerals, and mafic minerals, in line with the high volcanic activity. Based on ten species of the larger benthic foraminifera, tuffaceous limestone was deposited during the Early Miocene (Te5),  which led to the age of deposition of carbonate volcaniclastic rocks in the Cikarang Member of Jampang Formation. Meanwhile, the other three limestone types do not contain pyroclastic components, indicating low volcanic activity during their deposition and it was deposited during the Mio-Pliocene. Based on similarities in age, environment, and characteristics of grainstone, packstone, and boundstone types are grouped as part of the Cibodas Formation, which was deposited during the Late Miocene to Pliocene (Tf3–Th). This study contributes to understanding the stratigraphic differences and the geological history of the limestone in this region, highlighting the influence of volcanic and marine processes on limestone formation.Keywords: Limestone, Cikangkung, Cibodas Formation, Cikarang Member of Jampang Formation